Rancang Bangun Alat Ukur Kualitas Oli Kendaraan Dengan Mengukur Perubahan Viskositas Berbasis Internet Of Things (IOT) - Riki Desrianto; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In the field of machinery, both private-owned transportation or company- engaged in transportation, such as two-wheeled and four-wheeled vehicles. lubricant quality measurement is important in keeping the engine be durable and long-lasting, timely lubricant changing can save the maintenance cost and also provide driving comfortable, on the other hand, lubricant changes that is not on time can cause the engine be break quickly and lavish in maintenance costs, lubricant quality can be identified by measuring the changing of viscosity. In this study lubricants quality measurement tool is designed by measuring changes of viscosity based on Internet of Things, by knowing the changes of viscosity can determine the condition of each lubricant, by applying the internet of things technology on measurements can make monitoring be easier because measurement data are sent and stored in the database, by android application in monitor of the measurements using internet network whenever and wherever, from testing results using method, conducted on three different lubricants samples obtained that correlation relationship between voltage and viscosity with linear line equation namely: SAE 10W-30 lubricants are y = 6.4896x + 74,076, SAE 20W-40 oil are y = 9.11x + 154.61 and SAE 15W-30 lubricants are y = 16.013x + 129.8 where as x is the voltage and y is the viscosity the average error of each tool measurement is of lubricant quite good only 2.61%. Sending measurement data by arduino devices is also very good with an average delay less than 300ms.Keywords: Lubricants, Viscosity, Internet of Things.